Managing the Economy in a Post-Pandemic Future: The Case of Sukuk Issuing Countries - Nursilah Ahmad; Asma Abdul Rahman; Syazwani Abd. Rahim (Fakulti Ekonomi dan Muamalat, Universiti Sains Islam Malaysia, 2024)
Sukuk issuances play a critical role in promoting economic growth. The present study investigates the ‘three lows and one high’ of selected macroeconomic indicators in five major sukuk issuing countries for the period 2004 until 2021. The three lows refer to the inflation rate, unemployment rate, and overnight policy rate while ‘the one high’ denotes economic growth. These four macroeconomic indicators indicate the general overall health of an economy. The findings reveal that the four indicators' performance varies among countries under study, and each indicator has a different impact on each economy. In addition, the study analyses the growth components of GDP in these countries five years before the COVID-19 pandemic outbreak. The findings suggest that to boost sukuk market development, the policymakers should provide a comprehensive assessment of fiscal space during the COVID-19 crisis. Therefore, sound macroeconomic policies are key considerations for faster economic recovery post-pandemic.